Pedagogical construction grammar: The case of collocations and collostructions in foreign language instruction - Pakzadian, Maryam (AILA Review, 2023)
The concept of constructions has become increasingly important in theories of language acquisition and use during the last 20 years. Constructions are form-meaning pairings that are learned and stored as pieces of linguistic knowledge. Fillmore, Kay, and O'Conner (1988), and Goldberg (1995, 2006, 2019) were among the first linguists who paved the way for this alternative constructivist view on grammar. Since then, Construction Grammar (CxG) has become a widely accepted descriptive and processing model that is based on a large body of scientific research (e.g., Herbst, Schmid, & Faulhaber, 2014; Herbst, 2016; Hilpert, 2019; Hoffmann, 2022; Stefanowitsch, 2011). However, it is only recently that linguists have addressed the question of whether second/foreign language learners' linguistic competence depends on constructions (e.g., Boas, 2022; De Knop & Gilquin, 2016). If CxG is widely recognized in the branch of first language acquisition, it is also indispensable to transfer this concept to Applied Linguistics to design suitable teaching materials and methods. Drawing upon the proposition "foreign language learning is construction learning"(Ellis, 2001; Herbst, 2016), this article aims to suggest a proposal for teaching English collocations following Herbst's (2016) seven principles of Pedagogical Construction Grammar (PCxG). In particular, this article aims to suggest ways to apply these principles to developing supplementary teaching materials, activities, and tasks for teaching English collocations and collostructions.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Applied Construction Grammar; collocations; Construction Grammar; foreign language pedagogy; Pedagogical Construction Grammar